Associations of eczema phenotypes with emotional and behavioural problems from birth until school age. The Generation R Study. (1st August 2020) - Hu, C.; Nijsten, T.; Pasmans, S.G.M.A.; de Jongste, J.C.; Jansen, P.W.; Duijts, L.
Summary: Background: Eczema phenotypes and emotional and behavioural problems are highly prevalent in childhood, but their mutual relationship is not fully clear. Objectives: To examine the associations of eczema phenotypes with school‐age emotional and behavioural problems, and the bidirectional associations of eczema and emotional and behavioural problems from birth until 10 years. Methods: This study among 5265 individuals was embedded in a prospective population‐based cohort study. Never, early transient, mid‐transient, late transient and persistent eczema phenotypes were identified based on parent‐reported, physician‐diagnosed eczema from age 6 months until 10 years. Emotional (internalizing) and behavioural (externalizing) problems were measured repeatedly using the Child Behavior Checklist from age 1·5 to 10 years. Cross‐lagged models were applied for bidirectional analyses. Results: All eczema phenotypes were associated with more internalizing problems and attention problems at age 10 years, compared with never having eczema: range of Z ‐score differences 0·14 [95% confidence interval (CI) 0·01–0·27] to 0·39 (95% CI 0·18–0·60). Children with early transient eczema had more aggressive behaviour symptoms at age 10 years ( Z = 0·16, 95% CI 0·05–0·27). Bidirectional analysis showed that eczema at 0–2 years was associated with more internalizing and externalizing problems at ages 3–6 and 10 years, while, inversely, only internalizing problems at 0–2 years were associated with an increased risk of eczema at age 10 years. Conclusions: Eczema phenotypes are very modestly associated with more somatic symptoms and attention problems at school age. Early transient eczema is associated with more aggressive behaviour symptoms. Directional effects seem to occur from early‐life eczema to later‐life internalizing and externalizing problems, rather than the reverse.